History of Demography of Industrial Cities of Tashkent Region - Peremkulov Jamshid Allayerovich (Researchparks Publishing, 2021)
This article is devoted to the study of urbanization processes in industrial cities of Tashkent region such as Angren, Chirchiq, Almalyk and Bekabad by highlighting the population migration and related demographic changes in this area. The periodic limit of the article is set from the second quarter of the XX century to the beginning of the XXI century. The article focuses on the migration of these resource cities during the years of Soviet rule, and then the changes that happened during the years of independence. In addition, economic, social and political factors influencing changes in population dynamics were revealed. The article also highlightes the contradictions and problems in the Soviet government’s concepts for the construction of industrial cities. It is noted that due to the economic, social and political reforms carried out by the republic during the years of independence, the urbanization process in the studied cities is stabilizing.